Globalization in world history - Stearns, Peter N. (New York Routledge/Taylor & Francis Group, 2017)
"In this revised edition of globalization in World History, Peter Stearns explores the roots of contemporary globalization, examining shifts in the global flow of people, goods and ideas as early as 1000 CE. Exploring how four moments in history have accelerated the process of globalization, Stearn's narrative details how factors such as economics, migration, disease transmission, culture, the environment, and politics have influenced the nature of globalization as we understand it today" --Provided by publisher.
Globalization and the challenge to historical analysis -- Emerging patterns of contact, 1200 BCE-1000 CE : a preparatory phase -- 1000 CE as turning point : the birth of globalization? -- 1500 as turning point : the birth of globalization? -- The 1850s as turning point : the birth of globalization? -- Globalization since the 1940s : a new global history? -- Conclusion: The historical perspective.
Includes bibliographical references and index.
Keywords: Globalization -- History; World history; International economic relations -- History; Economic history; Human beings -- Migrations -- History; International relations -- History; Intercultural communication -- History; Culture diffusion -- History; Diseases and history